Mono-nuclear cis-Pd(II) chloride complex of the thio-nucleotide analogue 5-methyl-thiouracil and its biological activity. (17th February 2015) - Banti, C.N.; Charalampou, D.C.; Kourkoumelis, N.; Owczarzak, A.M.; Kubicki, M.; Hadjikakou, S.K.; Hadjiliadis, N.
Graphical abstract: The new palladium(II) complex cis-Cl- [PdCl2 (TPP)(MTUC)]·3(H2 O) (MTUC = 6-methyl-thiouracil and TPP = triphenylphosphine) was evaluated for its in vitro cytotoxicity against MCF-7 (breast) and HeLa (cervical) cancer cell lines. The binding affinity of1 towards DNA and lipoxygenase was also studied. Partial least squares regression analysis correlates the variation of the IC50 values with the variations of energetic parameters of1 and related palladium(II) complexes. Abstract: The new mixed ligand palladium(II) complex of formula cis-Cl- [PdCl2 (TPP)(MTUC)]·3(H2 O) (1 ) was obtained by reacting 6-methyl-thiouracil (MTUC) with triphenylphosphine (TPP). The complex was characterized by vibrational spectroscopy (FT-IR), 1 H NMR, UV–Vis spectroscopic techniques and its structure was confirmed by X-ray crystallography. Mixed ligand complexes of palladium(II) dichloride with thiones and phosphines are very rare in the literature. Compound1 is the fourth of this kind of compounds which has also been examined for its biological effects. Complex1 was evaluated for its in vitro cytotoxic activity (cell viability) against human cancer cell lines: MCF-7 (breast) and HeLa (cervical) with tryban blue assay. The results showed that1 mediates a mild cytotoxic response to the tested cancer cell lines. The binding affinity of1 towards the intracellular molecules DNA and lipoxygenase (LOX) was studied for the evaluation of the mechanism of its cytotoxicity. Partial least squares (PLS) regression analysis was carried out to correlate the variation of the IC50 values ( Y -variables) with the variations of energetic parameters ( X -variables), calculated from molecular docking calculation for1 and related palladium(II) complexes reported.